Fake ID - Giles, Lamar. 1979- (Amistad, an imprint of HarperCollins Publishers, 2015)
"An African-American teen in the Witness Protection Program moves to a new town and finds himself trying to solve a murder mystery when his first friend is found dead"--Provided by publisher.